The Making of Captains of Lives : Prison Reform in Singapore: 1999 to 2007. - Chua, Chin Kiat (World Scientific, 2012)
This book tells a story of successful prison reform that brought the recidivism rate of prisoners down from 44% to 24%. In the process of this reform, the entire Prison Service was transformed from a custody focused mindset to a rehabilitation centred culture. This change was wrought despite the lack of enthusiasm of the then political leadership. The author describes his personal role in the reform effort, the methodology used to engender change in organizational culture and the struggles for the soul of the prison service and the hearts and minds of all those involved. These include organiza.